Organizational Culture with Individual Readiness as a Mediator for Championing Behavior Electronic Medical Record Implementation - Ratna Wardani; Ulfa Tarbiati; Sri Suhandiah (Universitas STRADA Indonesia, 2024)
The dynamism of the application information technology in the health sector, especially in hospitals, which is currently being developed is the electronic medical record (EMR). Global competition in the era of industrial revolution 4.0 makes all hospitals have to be ready for the changes that will occur in the management of medical record management. This study aims to analyze the influence of organizational culture with individual readiness as a mediator on championing behavior in the implementation of electronic medical records (EMR) at Muhammadiyah Hospital. Respondents amounted to 133 people consisting of professional health workers who will later be involved implementation of EMR. The research instrument was in the form of a questionnaire via a google form link. Analysis using SEM (structural equation model) with Lisrel. The results showed that organizational culture significantly affected individual readiness (?=0.67, t-value=7.40). Organizational culture has a significant effect on championing behavior (?=0.42, t-value=4.10). Individual readiness significantly affects championing behavior (?=0.48 , t-value = 4.56). Individual readiness is also a significant mediator of the relationship between organizational culture and championing behavior (complementary mediation type). A strong organizational culture will support the readiness of the organization's planned changes. A strong organizational culture also influences behavior to fight for the success of the change plan. Through individual readiness, organizational culture influences behavior to fight for the successful implementation of EMR. So, organizations need to prepare individuals well for the success of the change plan. Keywords : Championing Behavior, EMR, Organizational Culture, Readiness for Change